PROTOTYPE WATER SPRAY OTOMATIS UNTUK PEMBERSIHAN DEBU BATUBARA PADA COAL CONVEYOR - Arik Putra Pratama; Nina Paramitha; Rasmila; Tamsir Ariyadi (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
Coal dust generated during the transfer process via belt conveyors at PT Bukit Asam Tbk has significant negative impacts on the environment and the health of workers. The current manual method, involving direct water spraying, is ineffective in controlling airborne dust and increases safety risks due to water exposure and unstable working conditions. To overcome these challenges, this study developed a prototype of an Arduino-based automatic water spraying system as a safer and more efficient solution.The system employs a SHARP GP2Y1010AU0F dust sensor to monitor coal dust concentrations in real-time and an HC-SR04 ultrasonic sensor to regulate water spraying automatically, based on the detected levels. The prototype was tested under operational conditions and showed optimal performance, effectively reducing coal dust concentrations while improving health and safety standards in the workplace.This innovation offers a practical and sustainable approach to coal dust management, addressing the shortcomings of manual methods. By automating the process, it minimizes worker exposure to dust and eliminates hazards associated with direct water application. The system's efficient and safe operation highlights its potential for broader implementation in similar mining environments. This technology not only resolves critical issues in coal dust control but also introduces a forward-thinking solution that aligns with industry goals for improved occupational safety and environmental protection.